Die saamspeel van hand, oog en passie: gedagtes oor erotiek en estetika - Veldsman, Daniël Petrus (Verbum et ecclesia, 2006)
In critical dismissal on the one hand of the viewpoint of Augustine on original sin, and on the other hand of a proposed viewpoint with regard to a theology of God’s good creation, this article explores the intimate interwoveness of aesthetics, erotism and religious experience. The basic communication structure of sender-message-receiver is taken as vantage point and translated into questions regarding the artist, the medium and the enjoyer of art / art critic. Against a historical-terminological background of aesthetics and erotism from Plato and Aristotle to contemporary views, a theological viewpoint is developed in playful metaphoric utilization of the concepts hand, eye and passion. Passion is acquitted in this viewpoint in which hamartological short-sightedness is replaced by loving far-sightedness.